ANALISIS PENDAPATAN USAHA JURAGAN TEH SELAMA BULAN RAMADHAN - Nila Mawangsari; Muh Amrih (LPPM Universitas Adiwangsa Jambi, 2024)
In the month of Ramadan, there is a significant increase in people's need for food and drinks to break the fast. The tradition of breaking the fast with family and friends creates high demand for refreshing drinks, one of which is tea. Tea sellers usually take advantage of this moment by increasing promotions, offering discounts, and providing special packages that attract consumers. There are several things that contribute to the phenomenon of increasing income for tea sellers during the month of Ramadan, making it a very profitable period for entrepreneurs in this field. The aim of this research is to analyze Juragan Teh's business income during the month of Ramadan and find out what factors influence the increase in income. This research uses a qualitative descriptive method where the data source is obtained by conducting interviews with Juragan Teh business owners and from observations made. Researchers also conducted trend analysis to determine the increase in income where the data source came from sales data in Juragan Teh's business. The results of this research state that during the month of Ramadan there was a significant increase in income for the Tea Juragan Business by 66% compared to the income of previous normal months. The results also show that there are several factors that influence the increase in Juragan Teh's business income, namely business capital, business location and working hours..